The Effect of Interpersonal Trust and Need of Achievement on the Lecturers’ Performance (Study at Universitas Muhammadiyah Ponorogo) - La Ode Sugianto; Titis Purwaningrum; Siti Chamidah (Universitas Muhammadiyah Ponorogo, 2020)
The study describes the effect of interpersonal trust and need of achievement on the performance of lecturers at Muhammadiyah University of Ponorogo. The results of the path analysis or hypothesis testing show that the effect of interpersonal trust on the lecturers’ performance is 66.8% and the increasing need of achievement also improve the performance of the lecturers at University Muhammadiyah of Ponorogo where the results of the path analysis of need of achievement towards the performance of the lecturers is 8.3%. Even though the variable need of achievement has not significantly affected the performance of the Muhammadiyah University of Ponorogo lecturers which is constructed with indicators of working hard, like challenging work, and setting goals. In addition, the contribution of Interpersonal trust and need of achievement to performance was 53.4%. Therefore it can be concluded that the performance variable is explained by Interpersonal trust and need of achievement is 53.4% while the rest is influenced by other variables which not included in this study.